Urbanisation and social cohesion: Theory and empirical evidence from Africa - Tekalign Gutu Sakketa (German Institute of Development and Sustainability (IDOS), 2023)
Africa is currently undergoing the most rapid urbanisation process globally, and this trend is forecast to persist in the coming decades. Many believe that this ongoing rapid urbanisation process is changing the social fabric and reshaping social cohesion. This study explores the theoretical channels through which urbanisation affects social cohesion and provides empirical evidence of their interrelationship. Specifically, the study asks: given the vast social, economic, cultural, political and environmental transformation associated with urbanisation, is there a link between urbanisation and social cohesion? Combining a novel national panel data set on social cohesion from Afrobarometer with urbanisation and other socioeconomic data from world development indicators, the study shows that urbanisation is negatively correlated with the three attributes of social cohesion, namely trust, inclusive identity, and cooperation for the common good. These associations persist even after controlling for country socioeconomic conditions and year fixed effects. Moreover, the magnitude of this association varies across attributes, with trust and inclusive identity showing a higher correlation than cooperation for the common good. Urbanisation-induced change in economic and environmental structure, such as employment, infrastructure, and pollution, are the main channels affecting social cohesion. Overall, the findings underscore the need for inclusive urban development and policies focused on ameliorating social fragmentation resulting from rapid urbanisation unfolding across Africa.
Keywords: 330; Urbanisation; social cohesion; trust; inclusive identity; cooperation for the common good; Africa